Ergonómia, bezpečnosť a ochrana zdravia na pracovisku so zobrazovacou jednotkou - RAJNICOVÁ, Henrieta (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2013)
Article is devoted to a safe job with the display unit, ergonomics in the workplaceand health problem, that are in long-term computing most often occur.